Project-Based Learning methodology (PBL) for the acquisition of Transversal Competences (TCs) and integration of Sustainable Development Goals (SDGs) in mechanical engineering subjects - Carlos Llopis-Albert; Francisco Rubio; Vicente Mata-Amela; Carlos Devece; María Eugenia Torner-Feltrer; Shouzhen Zeng (Multidisciplinary Journal for Education, Social and Technological Sciences)
This research is carried out within the framework of a two-year Educational Innovation and Improvement Project (EIIP) to be implemented at the Universitat Politècnica de València (UPV) during the academic years 2023-2024 and 2024-2025. The project aims to design and apply a Project-Based Learning methodology (PBL) for a proper acquisition of Transversal Competences (TCs) and integration of the Sustainable Development Goals (SDGs) in a mechanical engineering subject that is taught in the first year of the master’s degree in Mechatronic Engineering from the School of Design Engineering. Based on an assessment by the teaching staff of the current situation and the aspects to be improved, this article explains how the PBL methodology will be applied and performs an analysis through surveys and personal interviews with the students of their level of knowledge regarding the TCs and the SDGs that are worked on in the subject at the beginning of the academic year. The results show the need to continue working in the project and implementing active teaching techniques, such as PBL methodologies, to achieve a more attractive and motivating subject, closer to the labour market and a sustainable society.